THE ANALYSIS OF LEARNING STYLES IN DEVELOPING STUDENT LEARNING ACHIEVEMENT - Nurul Azizah; Muh. Fihris Khalik; Rizka Indahyanti (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2026)
Education plays a vital role in shaping intelligent, well-mannered, and competitive generations. One of the main factors determining students’ learning success is their learning style the unique way individuals receive, process, and understand information. Every student has different learning tendencies, whether visual, auditory, or kinesthetic. This study aims to identify the factors influencing the learning styles of fourth-grade students at SD Tamalanrea and to analyze how these learning styles contribute to improving their achievement in English. The study employs a qualitative approach with a case study design. Data were collected through closed questionnaires, semi-structured interviews, and documentation, referring to the VAK (Visual, Auditory, Kinesthetic) model by (Barbe et al., 1979) and the learning style factors theory proposed by (Rita & Dunn, 1993). The expected results reveal variations in students’ learning styles and a positive relationship between the alignment of teaching methods and students’ preferred learning styles toward enhancing English learning achievement. This research is expected to provide practical insights for teachers in understanding students’ learning characteristics and in developing more effective and student-centered teaching strategies.